2012
DOI: 10.4236/opj.2012.21001
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Optical Waveguide Bent Loss Attenuation Effects Analysis and Modeling Application to an Intrinsic Optical Fiber Temperature Sensor

Abstract: The temperature dependence of the bending loss light energy in multimode optical fibers is reported and analyzed. The work described in this paper aims to extend an initial previous analysis concerning planar optical waveguides, light energy loss, to circular optical waveguides. The paper also presents a novel intrinsic fiber optic sensing device base on this study allowing to measure temperatures parameters. The simulation results are validated theoretically in the case of silica/silicone optical fiber. A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…Results in Table 5 Table 6, the sensitivity of the sensor is increased when the bending diameter was reduced. The results obtained is agreed with [10,[15][16]. As the bending of the fiber increased, their sensitivity profile toward surrounding also increases.…”
Section: Increased the Simulation Time Also Increasessupporting
confidence: 80%
See 2 more Smart Citations
“…Results in Table 5 Table 6, the sensitivity of the sensor is increased when the bending diameter was reduced. The results obtained is agreed with [10,[15][16]. As the bending of the fiber increased, their sensitivity profile toward surrounding also increases.…”
Section: Increased the Simulation Time Also Increasessupporting
confidence: 80%
“…Results in Table 5 proves that as the bending radius getting smaller, less output power is captured since more lights was escaped from the fiber. The current finding in Table 5 is clearly supported by [10,[15][16]. In [15] s greater than 1.5cm, their bending losses is not significance.…”
Section: Increased the Simulation Time Also Increasessupporting
confidence: 77%
See 1 more Smart Citation
“…The curvature of the optical fiber is one aspect that is often used in the measurement system based on optical fiber sensor [4,19], while the imperfection will increase power losses that can cause increased sensitivity of the sensor [1,20]. The load sensor is made utilizing the principles by changes in light intensity due to the curvature on the optical fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Optical fiber-based sensor applications has grown rapidly and can be used to measure different variables, such as the measurement of the electric field, an electric current, cracking, load measurement, temperature, displacement, strain, pressure and so forth. Several studies have reported that optical fiber can be used for measurement of the electric current using the optical fiber-based curvature sensors [2], the sensor of a pre-stressed concrete viaduct for structural healt monitoring (SHM) [3], the application for the temperature sensor with power losses curvature [4], the application of optical fibers for displacement sensor [5,6], for a strain sensor [7] and the application of optical fibers as a pressure sensor [8]. Further research will focus on the measurement of weight using microbending methods on the optical fiber-based sensors and OTDR [9].…”
Section: Introductionmentioning
confidence: 99%